Factors predicting morbidity in surgically-staged high-risk endometrial cancer patients. (November 2021) - Bogani, Giorgio; Papadia, Andrea; Buda, Alessandro; Casarin, Jvan; Di Donato, Violante; Plotti, Francesco; Gasparri, Maria Luisa; Cimmino, Chiara; Pinelli, Ciro; Perrone, Anna Myriam; Barra, Fabio; Cromi, Antonella; et al.
Abstract: Objective: To investigate factors predicting the risk of developing 90-day postoperative complications and lymphatic-specific morbidity in patients undergoing surgical staging for high-risk endometrial cancer. Methods: This is a multi-institutional retrospective cohort study. Patients affected by apparent early-stage high-risk endometrial cancer (endometrioid FIGO grade 3 with deep myometrial invasion and non-endometrioid endometrial cancer) undergoing surgical staging between 2007 and 2019. Complications were graded according to the Clavien-Dindo classification system. Martin criteria were applied to improve quality of complications reporting. Results: Charts of 279 patients were evaluated. Lymphadenectomy, sentinel node mapping (SNM), and SNM followed by back-up lymphadenectomy were performed in 83 (29.7%), 50 (17.9%), and 146 (52.4%) patients, respectively. The former group of patients included 13 patients who had lymphadenectomy after the failure of the SNM technique. Thirteen (4.6%) patients developed severe postoperative events (grade 3 or worse). At multivariate analysis, body mass index (OR: 1.08 (95%CI: 1.01, 1.17)) and open abdominal surgery (OR: 2.27 (95%CI: 1.02, 5.32)) were the two independent factors predictive of surgery-related morbidity. Seven severe lymphatic complications occurred. The adoption of laparoscopic approach (p < 0.001, log-rank test) and SNM (p = 0.038, log-rank test) correlated with a lower risk of developing surgery-related events. Independently, open abdominal surgery was associated with an increased risk of developing lymphatic morbidity (OR: 37.4 (95%CI: 4.38, 319.5); p = 0.001). Conclusion: The adoption of the laparoscopic approach and SNM technique were associated with lower 90-day complication rates than open surgery in high-risk endometrial cancer undergoing staging surgery.